Glycemic and metabolic sub-classification of prediabetes and risk factors for cardiovascular disease in the D2d cohort - Sangeeta R. Kashyap; Cyrus Desouza; Vanita R. Aroda; Sun H. Kim; Lisa M. Neff; Shannon S. Wu; Philip Raskin; Richard Pratley (Elsevier, 2023)
Objectives: Prediabetes represents a spectrum of metabolic abnormalities, including insulin resistance and secretory impairment, that carries increased cardiovascular disease (CVD) risk. It is unclear whether specific glycemic and metabolic sub-classifications are associated with CVD risk. This cross-sectional analysis of 3946 participants from the Vitamin D and Type 2 Diabetes (D2d) study cohort aimed to determine the associations between various baseline CVD risk factors, glycemic sub-classifications of prediabetes (FPG, 2hPG, and HbA1c), and measures of insulin sensitivity and secretion from an OGTT. Methods: The metabolic syndrome and atherosclerotic cardiovascular disease (ASCVD) risk scores were determined for tertiles of insulin sensitivity (HOMA2S) and insulinogenic index (IGI). Unadjusted analyses showed elevated CVD risk factors in the lowest tertile for both IGI and HOMA2S. Results: After adjustment for age, gender, race, obesity, and smoking status, the association remained between HOMA2S and ASCVD score (r = -0.11, p< 0.001) but not for IGI. Those who met at least 2 diagnosic criteria for prediabetes had the largest proportion (> 40%) of participants with high ASCVD risk score >20. A higher percentage of individuals that met all 3 criteria for prediabetes had metabolic syndrome and ASCVD risk score >20 (87.2% and 15.3%, respectively) than those who only met 1 prediabetes criterion (51.6% and 7.1%, respectively). Conclusions: In conclusion, multiple metabolic (HOMA2S, IGI) and glycemic criteria of prediabetes (FPG, 2hPG, & HbA1c) are needed to fully recognize the elevated CVD risk profile that can manifest in prediabetes.